Influence of English Memes regarding Critical Digital Literacy - Arroyave Madrigal, Yuliana; Vargas Martínez, Santiago Alberto (Universidad Cátolica Luis Amigó, 2021)
While literacy practices have changed around the world, this paper mentions how students from Universidad Catolica Luis Amigo have improved their literacy skills through interacting with english memes and how english memes have started to promote Critical Digital Literacy. Therefore during this research was made some analysis in order to identify how actually this practice influence the Critical Digital Literacy Development using case studies as method for this research in order to have a better analysis of the information, the data análisis found led to the conclusion that English memes are useful for developing and improve critical Digital Literacy on students being this a new communicative and literary practice.
Keywords: Literacy; Memes; Education; Literacy practice; a